Correlation between Sensory and Texture Evaluation of Chaoshan Crisp Meatballs - Shuchang LI; Minmin AI; Jiaoli LONG; Shiyang HUANG; Zehao FANG; Shanguang GUO; Hong FAN; Yuanyuan CAO; Quan ZHOU; Aimin JIANG (Shipin gongye ke-ji, 2022)
: Objective：A comprehensive evaluation method was utilized to explore for the brittleness quality of Chaoshan crisp meatballs. Method: Textural profile analysis and puncture test were used to determine the textural property of Chaoshan crisp meatballs, and sensory evaluation were carried out simultaneously, and the correlation analysis between sensory and instrumental evaluation was studied. Result: The TPA parameters, including hardness and chewiness, were significantly correlated with the sensory evaluation parameters about hardness, springiness, brittleness and chewiness (r=0.554~0.793, P<0.05). The resilience of TPA was significantly correlated with the texture brittleness and organization of sensory evaluation (r=0.556, 0.625, P<0.05). The breaking force of puncture test was significantly correlated with sensory evaluation indexes (r=0.595~0.709, P<0.05). Two main components were obtained by PCA (principal component analysis) of the texture evaluation data, and their cumulative variance contribution rate was 74.5%. Conclusion: Therefore, the brittleness quality of Chaoshan crisp meatballs could be evaluated comprehensively by the combination of hardness and chewiness of TPA, breaking force in puncture test and sensory evaluation, which would lay the foundation for constructing an objective, accurate and convenient sensory evaluation system for Chaoshan crisp meatballs.